Distance education and distributed learning - Vrasidas, Charalambos; Glass, Gene V., 1940- (Current perspectives on applied information technologies., 2002)
This work discusses issues relating to distance education and distributed learning. There are essays covering: rethinking assessment for the online environment; the role of collaborative learning in social and intellectual development; and the embodiment of knowledge in virtual environments.